Tingkat Kapitalisasi Tanah Kosong di Kota Denpasar - Budi Purnomo (Melati Institute, 2023)
The capitalization rate is the ratio between the rental income and the selling price of the land. The greater the capitalization rate of the land, the more potential investors are interested in buying the land. The capitalization rate of vacant land from one region to another is not the same, depending on the economic development of each region and the need/competition for the desire to own the land. This is in line with one of the characteristics of land, which is its unique nature ((source: Supardi et al. (2010)). Land that exists in one area with other areas has its own characteristics and characteristics. Therefore, it is very interesting and important to conduct further studies to determine the level of capitalization of vacant land in Denpasar City. This capitalization rate is used to calculate the rental price of vacant land based on the selling price of the land. This research uses descriptive statistical analysis tools. The calculation of the capitalization rate uses sales / offer data and rental / lease transaction data on vacant land as much as 72 (seventy-two) data. The conclusion of this study is that the average capitalization rate of vacant land in Denpasar City is 1.03% (ceteris paribus) and according to zoning, the capitalization rate of vacant land for commercial (1.117%) is higher than for residential (0.981%).